Rainwater Harvesting for Drought Disaster Prevention in Seraya Village, Karangasem Regency, Bali Province, Indonesia - Putu Doddy Heka Ardana; Tri Hayatining Pamungkas; I Gede Adi Alit Putra (Journal of the Civil Engineering Forum, 2025)
Drought is a recurring disaster in several regions of Indonesia, often happening from April to September annually. During the dry season, a substantial reduction in rainfall leads to inadequate water supplies and drought. Drought significantly affects food crop output, water scarcity, and reduced water availability for daily necessities, disrupting everyday activities like bathing, washing, and cooking. Seraya Village, situated in Karangasem Regency, Bali Province, frequently faces drought conditions. Seraya, a settlement prone to drought, was officially designated as such by the Karangsem Regent by Regulation Number 36 of 2008, specifying the location of drought natural disasters in Seraya settlement, East Seraya, and West Seraya in the Karangasem District. This study aimed to compare the capacity of rainwater harvesting with the current home water demand in Seraya-Karangasem Village to determine the feasibility of using rainwater to address water shortages and avert drought. This study employs quantitative descriptive methods by analyzing primary data on the regional conditions and limits of the study area, along with secondary data on demographic (population), geographical, and rainfall data spanning a decade. The study revealed that the rainwater harvesting potential in Seraya Village, Karangasem District, was 254342191.15 liters per year, while the total water demand was 227660565 liters yearly. This resulted in excess harvested water amounting to 26681626.15 liters per year, 12% more than the total water needs. The excess amount of rainwater that may be harvested compared to the entire domestic water demand demonstrates the effective utilization of rainwater harvesting systems in preventing water shortages and droughts in Seraya-Karangasem Village.